A preparation method of a C-band low-frequency electromagnetic wave absorption coating
Patent Information
- Application Number
- CN202311358874.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-10-19
AI Technical Summary
然而铁氧体的复磁导率实部和复介电常数实部较小、饱和磁化强度低、面密度大、居里温度低以及高温稳定性差,导致其应用范围受到限制
[0032]此外,本发明将具有片状形貌的介孔磁性金属与类石墨烯的二维层状过渡金属硫化物进行复合,制备新型异质结构复合电磁波吸收剂。一方面片状形貌磁性金属大的宽厚比可以带来强的形状各向异性,从而有效突破Snoke极限获得更高的低频磁导率。另一方面,类石墨烯的二维层状过渡金属硫化物由于其独特的电子结构和显著的各向异性,使其在材料领域受到人们的广泛关注。由于硫元素化学性质非常活跃,能与多种元素结合,因此过渡金属硫化物的类型也较多,这里用通式MS2(X=Mo,W,Se)来表示。单分子层的MS2由上下两层硫原子夹着中间一层过渡金属原子通过共价键连接而成,层内强大的共价键赋予MS2良好的机械强度以及优异的化学稳定性和热稳定性。MS2纳米片具有大的比表面积,可以诱导产生极化电荷和强的界面极化作用,并获得高的介电损耗,从而有利于电磁波的吸收。通过将片状的磁性金属和二维层状过渡金属硫化物复合,构筑具有丰富界面相互作用的双相异质结构,利用复合材料体系的微观层级结构和多样化的电磁波损耗机制,可实现对电磁参数在C波段内的有效调控。此外,通过双层阻抗渐变吸波涂层的结构设计和优化,可以有效提升吸波涂层的阻抗匹配特性,通过增加谐振点拓宽在C波段的有效吸收带宽。
Smart Images

Figure CN117915641B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology, specifically relating to a method for preparing a C-band low-frequency electromagnetic wave absorber and coating. Background Technology
[0002] With the advancement and maturation of fifth-generation (5G) wireless technology, the global intelligent development process has been greatly accelerated. However, electromagnetic interference radiated by 5G devices and base stations has become ubiquitous electromagnetic pollution, leading to a deteriorating electromagnetic environment in human living spaces. Unlike traditional high-frequency radar electromagnetic waves, 5G electromagnetic signals are mainly located in the C-band (4-8 GHz) and below. Therefore, developing C-band electromagnetic wave absorbing materials is crucial for solving the electromagnetic pollution generated by 5G communication. Compared with high-frequency radar waves, the C-band has a lower frequency and a longer wavelength. In the same material system, low-frequency electromagnetic waves have better impedance matching performance, but the reflectivity of general material absorbing coatings is relatively high in the low-frequency band. That is, after low-frequency waves enter the absorbing coating and are reflected by an ideal metal plate, the radar wave energy emitted from the front interface of the coating is relatively large. Especially in the C-band, it is difficult for absorbing materials to meet the requirements of high-efficiency absorption performance with a small thickness. Therefore, reducing the thickness of the absorbing coating while ensuring absorption performance is a key research focus and challenge. Currently, low-frequency absorbing materials are mainly based on magnetic material systems such as ferrite or magnetic metal powders. However, ferrites have small real parts of complex permeability and complex permittivity, low saturation magnetization, high areal density, low Curie temperature, and poor high-temperature stability, which limits their application range. Although metallic magnetic materials have high saturation magnetization, they have poor corrosion resistance and oxidation resistance, and single-component electromagnetic wave absorbing materials share common problems such as poor impedance matching and narrow effective absorption bandwidth. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing a coating for absorbing low-frequency electromagnetic waves in the C-band, characterized in that:
[0004] 1) Add oxalic acid, thiourea, and selenium, tungsten, or molybdenum salts containing ammonium ions to deionized water to obtain a mixed solution;
[0005] 2) Transfer the mixed solution obtained in step 1) into a reaction vessel, heat the reaction for 24-48°C, and then allow it to cool naturally to room temperature;
[0006] 3) Obtain the grayish-black product from the bottom of the reactor in step 2) and wash it;
[0007] 4) Dry the product obtained in step 3) to obtain transition metal dichalcogenide nano-self-assembled bodies;
[0008] 5) The transition metal disulfide self-assembly was ultrasonically dispersed in deionized water, and then metal chloride and hexamethylenetetramine were added sequentially and stirred to react.
[0009] 6) Transfer the mixed solution from step 5) to a reactor for heating and reaction, separate the reaction products and wash them;
[0010] 7) Dry the product obtained in step 6) to obtain a transition metal disulfide and metal hydroxide composite precursor;
[0011] 8) The product obtained in step 7) is subjected to microwave treatment in a mixed gas atmosphere of argon and hydrogen to obtain a binary composite absorber of transition metal disulfide and magnetic metal.
[0012] 9) Using the product obtained in step 8) as the raw material for the coating, the coating is sprayed onto the substrate to obtain a C-band low-frequency electromagnetic wave absorbing coating.
[0013] Further, in step 1), the molar ratio of ammonium ion salt, oxalic acid, and thiourea is (0.5–2):(5–20):(20–80); further, in this step, 0.5–2 mmol of selenium salt, tungsten salt, and molybdenum salt containing ammonium ions (NH4+), 5–20 mmol of oxalic acid, and 20–80 mmol of thiourea are weighed in sequence and added to 50–200 ml of deionized water, and the mixture is magnetically stirred at room temperature for 10–30 minutes.
[0014] Furthermore, in step 1), the tungsten salt, molybdenum salt, and selenium salt containing ammonium ions (NH4+) are ammonium tungstate, ammonium molybdate, and ammonium selenate, respectively.
[0015] Furthermore, in step 2), the reactor is a polytetrafluoroethylene reactor, and the heating reaction is carried out at 180-240°C for 24-48 hours. After the reaction is completed, it is naturally cooled to room temperature.
[0016] Further, in step 3), the supernatant of the reactant obtained in step 2) is discarded, the gray-black product at the bottom of the reaction vessel is collected, the product is washed 3 to 5 times with anhydrous ethanol, and centrifuged at 5000 rpm for 5 to 10 minutes.
[0017] Further, in step 4), the product obtained in step 3) is vacuum dried at 50–80 °C for 12–24 hours to obtain transition metal dichalcogenide nano-self-assembled bodies.
[0018] Furthermore, in step 4), depending on the raw materials, the obtained transition metal disulfide nano-self-assembled body is tungsten disulfide, molybdenum disulfide, or selenium disulfide nano-self-assembled body.
[0019] Further, in step 5), the molar ratio of transition metal disulfide, metal chloride, and hexamethylenetetramine is (0.5–2):(5–20):(50–100). Further, in this step, 0.5–2 mmol of the transition metal disulfide self-assembly is weighed and ultrasonically dispersed in 500–2000 ml of deionized water, then 5–20 mmol of metal chloride and 50–100 mmol of hexamethylenetetramine are added sequentially, and the mixture is magnetically stirred at room temperature for 10–30 minutes; wherein the ultrasonic dispersion time of the transition metal disulfide self-assembly is 20–30 minutes, and the metal chloride is cobalt chloride, nickel chloride, ferric chloride, or a mixture of two of them.
[0020] Furthermore, in step 6), the heating temperature is 80-100℃, the reaction time is 1-2 hours, and after the reaction is completed, the solution is allowed to cool naturally to room temperature, vacuum filtered, and then washed 3-5 times with anhydrous ethanol and deionized water respectively.
[0021] Further, in step 7), the product obtained in step 6) is vacuum dried at 50-80°C for 8-12 hours to obtain the composite precursor;
[0022] Further, in step 8), the transition metal disulfide and metal hydroxide composite precursor obtained in step 7) is placed in a quartz boat, and a vacuum is applied for 10-20 minutes to maintain a low-pressure environment inside the quartz tube. Then, a mixture of argon and hydrogen is introduced, with the argon flow rate controlled at 100-200 sccm and the hydrogen flow rate controlled at 50-100 sccm. After introducing the mixed gas for 10-20 minutes, the microwave generator is turned on, with a microwave operating frequency of 2450 MHz and an output power of 700-1000 W, and the reaction time is maintained for 10-20 minutes. Then, the hydrogen source is turned off, and the mixture is cooled to room temperature in an argon atmosphere to obtain the transition metal disulfide and magnetic metal binary composite absorber.
[0023] Furthermore, in step 9), the following steps are included when obtaining the coating:
[0024] 9-1) The transition metal dichalcogenide magnetic metal composite absorber prepared in step 8) is mixed with epoxy resin and then dispersed.
[0025] 9-2) Dissolve the epoxy resin curing agent imidazole in a n-butanol solution, with a mass ratio of imidazole to n-butanol of 1:1;
[0026] 9-3) Mix the products obtained in steps 9-1) and 9-2) to obtain a coating;
[0027] In the above steps, when preparing the coating for the first layer, the composite absorbent is 5-10 parts, the epoxy resin is 82-86 parts, and the imidazole solution is 8-9 parts;
[0028] In the above steps, when preparing the coating for the second layer, the composite absorbent is 10-15 parts, the epoxy resin is 77-82 parts, and the imidazole solution is 8-9 parts.
[0029] Furthermore, in step 9), when preparing the double-layer electromagnetic wave absorbing coating, the spraying thickness of the first layer is 1.8–2.1 mm; the spraying thickness of the second layer is 1.8–2.1 mm; and the total thickness of the two electromagnetic wave absorbing layers does not exceed 4 mm.
[0030] Furthermore, in step 9), when the coating is formed by spraying, the substrate is an aluminum substrate, and an air spraying process is used to obtain a double-layer electromagnetic wave absorbing coating. After spraying, it is placed at room temperature for 1-2 hours, and then placed in an oven at 70-100°C for 1-2 hours for curing. This results in a coating with excellent absorption performance for low-frequency C-band electromagnetic waves.
[0031] This invention utilizes a homogeneous precipitation method to prepare metal hydroxides with micron-sized and uniformly distributed dimensions. The metal hydroxides are then reduced using microwave plasma-assisted reduction to obtain sheet-like magnetic metals and their alloys. Since microwave heating generates "internal frictional heat" through the high-frequency reciprocating motion of internal polar molecules, raising the temperature of the precursor molecules without any heat conduction process, simultaneous external heating and temperature rise are achieved. The heating speed is fast and uniform, preventing the collapse of the sheet-like structure of the hydroxide precursor due to heat conduction during the reduction process. Therefore, microwave plasma-assisted reduction technology ensures the effective inheritance of the sheet-like microstructure of the precursor.
[0032] Furthermore, this invention combines mesoporous magnetic metals with sheet-like morphology with graphene-like two-dimensional layered transition metal sulfides to prepare novel heterostructure composite electromagnetic wave absorbers. On one hand, the large aspect ratio of sheet-like magnetic metals can lead to strong shape anisotropy, effectively overcoming the Snoke limit to obtain higher low-frequency permeability. On the other hand, graphene-like two-dimensional layered transition metal sulfides have attracted widespread attention in the materials field due to their unique electronic structure and significant anisotropy. Because sulfur is chemically very reactive and can combine with many elements, there are many types of transition metal sulfides, which are represented here by the general formula MS2 (X = Mo, W, Se). The monolayer MS2 consists of two layers of sulfur atoms sandwiching a middle layer of transition metal atoms connected by covalent bonds. The strong covalent bonds within the layer endow MS2 with good mechanical strength, excellent chemical stability, and thermal stability. MS2 nanosheets have a large specific surface area, which can induce polarization charges and strong interfacial polarization, resulting in high dielectric loss, thus facilitating electromagnetic wave absorption. By compositing sheet-like magnetic metals with two-dimensional layered transition metal sulfides, a two-phase heterostructure with rich interfacial interactions is constructed. Utilizing the microscopic hierarchical structure and diverse electromagnetic wave loss mechanisms of the composite material system, effective control of electromagnetic parameters in the C-band can be achieved. Furthermore, through the structural design and optimization of a double-layer impedance-gradient absorbing coating, the impedance matching characteristics of the absorbing coating can be effectively improved, and the effective absorption bandwidth in the C-band can be broadened by increasing the resonant point. Attached Figure Description
[0033] Figure 1 Scanning electron microscope image of the WS2@Co binary composite absorbent prepared in Example 1 of this invention;
[0034] Figure 2 Transmission electron microscope image of the WS2@Co binary composite absorbent prepared in Example 1 of this invention;
[0035] Figure 3 The reflection loss diagram in Embodiment 1 of the present invention;
[0036] Figure 4 : Reflection loss diagram in Embodiment 2 of the present invention.
[0037] Figure 5 The reflection loss diagram in Embodiment 3 of the present invention;
[0038] Figure 6 : Reflection loss diagram in Embodiment 4 of the present invention. Detailed Implementation
[0039] The present invention will be further described below with reference to embodiments, but it should not be construed that the scope of the present invention is limited to the following embodiments. Various substitutions and modifications made based on ordinary technical knowledge and common practices in the art without departing from the above-described technical concept of the present invention should be included within the scope of protection of the present invention.
[0040] Example 1:
[0041] The purpose of this invention is to provide an electromagnetic absorber with high absorption performance in the C-band (4-8 GHz) and a method for preparing the coating. The method is characterized by the following steps: 1) Weigh 1 mmol of ammonium tungstate, 10 mmol of oxalic acid and 60 mmol of thiourea in sequence and add them to 80 ml of deionized water. Stir magnetically at room temperature for 20 minutes and then transfer the mixture into a polytetrafluoroethylene reactor.
[0042] 2) React the product obtained in step 1 at 220°C for 48 hours, and then allow it to cool naturally to room temperature;
[0043] 3) Discard the supernatant of the reactants obtained in 2), collect the gray-black product at the bottom of the reactor, wash the product 4 times with anhydrous ethanol, and centrifuge at 5000 rpm for 10 minutes.
[0044] 4) The product obtained in step 3) was vacuum dried at 60°C for 8 hours to obtain WS2 nano self-assembled bodies;
[0045] 5) Weigh 1 mmol of WS2 self-assembled compound and add it to 1000 ml of deionized water. Sonicate for 30 minutes. Then add 10 mmol of cobalt chloride and 80 mmol of hexamethylenetetramine in sequence, and stir magnetically for 20 minutes at room temperature.
[0046] 6) Transfer the mixed solution obtained in step 5) to a three-necked flask and heat it in an oil bath at 90°C for 2 hours. After the reaction is complete, allow the solution to cool naturally to room temperature and then filter it under vacuum.
[0047] 7) Wash the product obtained in step 6) three times with anhydrous ethanol and deionized water respectively; dry the product under vacuum at 60℃ for 8 hours to obtain the WS2@Co(OH)2 composite precursor; 8) Weigh 5g of the WS2@Co(OH)2 composite precursor and place it in a quartz boat, and evacuate for 15 minutes to maintain a low-pressure environment inside the quartz tube. Then, introduce a mixed gas of argon and hydrogen, with the argon flow rate controlled at 200sccm and the hydrogen flow rate controlled at 100sccm. After introducing the mixed gas for 10 minutes, turn on the microwave generator, with a microwave operating frequency of 2450MHz and an output power of 700W, and maintain the reaction time for 15 minutes. Then, turn off the hydrogen source and cool to room temperature in an argon atmosphere to obtain the WS2@Co binary composite absorbent.
[0048] 9) A double-layer electromagnetic wave absorbing coating was prepared using an aluminum plate as the base metal layer and an air spraying process. The WS2@Co binary composite absorber was mixed with epoxy resin and dispersed using a planetary ball mill at 5000 rpm for 5 minutes. Imidazole, the epoxy resin curing agent, was dissolved in a n-butanol solution at a mass ratio of 1:1 and then added to the WS2@Co binary composite absorber and epoxy resin mixture. The first layer consisted of 5 parts binary composite absorber, 86 parts epoxy resin, and 9 parts imidazole solution, with a spray thickness of 1.8 mm. The second layer consisted of 10 parts binary composite absorber, 82 parts epoxy resin, and 8 parts imidazole solution, with a spray thickness of 1.9 mm. After spraying, the coating was left at room temperature for 2 hours and then cured in an oven at 80°C for 2 hours. The effective absorption bandwidth (RL≤-10dB) ranged from 4.08 GHz to 7.92 GHz, covering almost the entire C-band.
[0049] Meanwhile, the reflection loss curve exhibits two resonant peaks, with the reflection loss at 4.8 GHz being [missing information].
[0050] -27.5dB, with a reflection loss of -25.4dB at 6.8GHz.
[0051] Example 2:
[0052] 1) Weigh out 1 mmol of ammonium molybdate, 10 mmol of oxalic acid, and 60 mmol of thiourea in sequence and add them to the solution.
[0053] Add 80ml of deionized water and stir magnetically for 20 minutes at room temperature;
[0054] 2) Transfer the product obtained in step 1) into a polytetrafluoroethylene reactor and heat it at 220°C.
[0055] The reaction was carried out for 48 hours, and then allowed to cool naturally to room temperature.
[0056] 3) Discard the supernatant of the reactants obtained in 2), collect the gray-black product at the bottom of the reactor, wash the product 4 times with anhydrous ethanol, and centrifuge at 5000 rpm for 10 minutes.
[0057] 4) The product obtained in step 3) was vacuum dried at 60°C for 8 hours to obtain MoS2 nano-self-assembled bodies;
[0058] 5) Weigh 1 mmol of MoS2 self-assembled body and add it to 1000 ml of deionized water, and sonicate for 30 minutes. Then add 10 mmol of cobalt chloride and 80 mmol of hexamethylenetetramine in sequence, and stir magnetically for 20 minutes at room temperature.
[0059] 6) Transfer the mixed solution obtained in step 5) into a three-necked flask and heat it in an oil bath at 90°C for 2 hours. After the reaction is complete, allow the solution to cool naturally to room temperature and then filter it under vacuum. Then wash it three times with anhydrous ethanol and deionized water, respectively.
[0060] 7) The product obtained in step 6) was vacuum dried at 60°C for 8 hours to obtain the MoS2@Co(OH)2 composite precursor;
[0061] 8) Weigh 5g of MoS2@Co(OH)2 composite precursor and place it in a quartz boat. Evacuate the quartz tube for 15 minutes to maintain a low-pressure environment. Then, introduce a mixture of argon and hydrogen gas, with the argon flow rate controlled at 200 sccm and the hydrogen flow rate controlled at 100 sccm. After introducing the mixed gas for 10 minutes, turn on the microwave generator with a microwave operating frequency of 2450MHz and an output power of 700W, and maintain the reaction time for 15 minutes. Then, turn off the hydrogen gas source and cool to room temperature in an argon atmosphere to obtain the MoS2@Co binary composite absorbent.
[0062] 9) A double-layer electromagnetic wave absorbing coating was prepared using an aluminum plate as the base metal layer and an air spraying process. The MoS2@Co binary composite absorber was mixed with epoxy resin and dispersed using a planetary ball mill at 5000 rpm for 5 minutes. The epoxy resin curing agent, imidazole, was dissolved in a 1:1 mass ratio of imidazole to n-butanol solution and then added to the MoS2@Co binary composite absorber and epoxy resin mixture. The first layer consisted of 5 parts binary composite absorber, 86 parts epoxy resin, and 9 parts imidazole solution, with a spray thickness of 1.8 mm. The second layer consisted of 10 parts binary composite absorber, 82 parts epoxy resin, and 8 parts imidazole solution, with a spray thickness of 2.1 mm. After spraying, the coating was left at room temperature for 2 hours and then cured in an oven at 80°C for 2 hours.
[0063] The effective absorption bandwidth (RL≤-10dB) ranges from 4.64GHz to 8.40GHz, almost covering the entire C-band. Meanwhile, the reflection loss curve exhibits dual resonant peaks, with a reflection loss of -23.0dB at 4.8GHz and -49.0dB at 7.2GHz.
[0064] Example 3:
[0065] 1) Weigh out 1 mmol of ammonium tungstate, 10 mmol of oxalic acid, and 60 mmol of thiourea in sequence and add them to 80 ml of deionized water. Stir magnetically for 20 minutes at room temperature.
[0066] 2) Transfer the product obtained in step 1) into a polytetrafluoroethylene reactor and react at 220°C for 48 hours, then allow it to cool naturally to room temperature;
[0067] 3) Discard the supernatant of the reactants obtained in 1), collect the gray-black product at the bottom of the reactor, wash the product 4 times with anhydrous ethanol, and centrifuge at 5000 rpm for 10 minutes.
[0068] 4) The product obtained in step 3) was vacuum dried at 60°C for 8 hours to obtain WS2 nano self-assembled bodies;
[0069] 5) Weigh 1 mmol of WS2 self-assembled compound and add it to 1000 ml of deionized water. Sonicate for 30 minutes. Then add 5 mmol of cobalt chloride, 5 mmol of ferric chloride and 80 mmol of hexamethylenetetramine in sequence, and stir magnetically at room temperature for 20 minutes.
[0070] 6) Transfer the mixed solution obtained in step 5) to a three-necked flask and heat it in an oil bath at 90°C for 2 hours. After the reaction is complete, allow the solution to cool naturally to room temperature and then filter it under vacuum.
[0071] 7) The product obtained in step 6) was washed three times with anhydrous ethanol and deionized water respectively; the product was dried under vacuum at 60°C for 8 hours to obtain the WS2@Co(OH)2 / Fe(OH)3 composite precursor.
[0072] 8) Weigh 5g of WS2@Co(OH)2 / Fe(OH)3 composite precursor and place it in a quartz boat. Evacuate the quartz tube for 15 minutes to maintain a low-pressure environment. Then, introduce a mixture of argon and hydrogen gas, with the argon flow rate controlled at 200 sccm and the hydrogen flow rate controlled at 100 sccm. After introducing the mixed gas for 10 minutes, turn on the microwave generator with a microwave operating frequency of 2450MHz and an output power of 700W, and maintain the reaction time for 15 minutes. Then, turn off the hydrogen source and cool to room temperature in an argon atmosphere to obtain the WS2@Co / Fe ternary composite absorbent.
[0073] 9) A double-layer electromagnetic wave absorbing coating was prepared using an aluminum plate as the bottom metal layer and an air spraying process. The WS2@Co / Fe ternary composite absorber was mixed with epoxy resin and dispersed using a planetary ball mill at 5000 rpm for 5 minutes. The epoxy resin curing agent imidazole was dissolved in a n-butanol solution at a mass ratio of 1:1, and then added to the mixture of WS2@Co / Fe ternary composite absorber and epoxy resin.
[0074] The first layer consists of 5 parts ternary composite absorbent, 86 parts epoxy resin, and 9 parts imidazole solution, with a spray thickness of 1.9 mm. The second layer consists of 10 parts ternary composite absorbent, 82 parts epoxy resin, and 8 parts imidazole solution, with a spray thickness of 2.0 mm. After spraying, the coating is left at room temperature for 2 hours, then cured in an oven at 80°C for 2 hours. The effective absorption bandwidth (RL≤-10dB) ranges from 4.08 GHz to 7.92 GHz, almost covering the entire C-band. Simultaneously, the reflection loss curve exhibits dual resonant peaks, with a reflection loss of -30.1 dB at 4.8 GHz and -26.2 dB at 6.8 GHz.
[0075] Example 4:
[0076] 1) Weigh out 1 mmol of ammonium molybdate, 10 mmol of oxalic acid, and 60 mmol of thiourea in sequence and add them to 80 ml of deionized water. Stir magnetically at room temperature for 20 minutes.
[0077] 2) Transfer the product obtained in step 1) into a polytetrafluoroethylene reactor and react at 220°C for 48 hours, then allow it to cool naturally to room temperature;
[0078] 3) Discard the supernatant of the reactants obtained in 1), collect the gray-black product at the bottom of the reactor, wash the product 4 times with anhydrous ethanol, and centrifuge at 5000 rpm for 10 minutes.
[0079] 4) The product obtained in step 3) was vacuum dried at 60°C for 8 hours to obtain MoS2 nano-self-assembled bodies;
[0080] 5) Weigh 1 mmol of MoS2 self-assembled body and add it to 1000 ml of deionized water, and sonicate for 30 minutes. Then add 5 mmol of cobalt chloride, 5 mmol of ferric chloride and 80 mmol of hexamethylenetetramine in sequence, and stir magnetically at room temperature for 20 minutes.
[0081] 6) Transfer the mixed solution obtained in step 5) into a three-necked flask and heat it in an oil bath at 90°C for 2 hours. After the reaction is complete, allow the solution to cool naturally to room temperature and then filter it under vacuum. Then wash it three times with anhydrous ethanol and deionized water, respectively.
[0082] 7) The product obtained in step 6) was vacuum dried at 60°C for 8 hours to obtain MoS2@Co(OH)2 /
[0083] Fe(OH)3 complex precursor;
[0084] 8) Weigh 5g of MoS2@Co(OH)2 / Fe(OH)3 composite precursor and place it in a quartz boat. Evacuate the quartz tube for 15 minutes to maintain a low-pressure environment. Then, introduce a mixture of argon and hydrogen gas, with the argon flow rate controlled at 200 sccm and the hydrogen flow rate controlled at 100 sccm. After introducing the mixed gas for 10 minutes, turn on the microwave generator with a microwave operating frequency of 2450MHz and an output power of 700W, and maintain the reaction time for 15 minutes. Then, turn off the hydrogen source and cool to room temperature in an argon atmosphere to obtain the MoS2@Co / Fe ternary composite absorber; 9) Prepare a double-layer electromagnetic wave absorbing coating using an air spraying process with an aluminum plate as the bottom metal layer. The MoS2@Co / Fe ternary composite absorbent was mixed with epoxy resin and dispersed using a planetary ball mill at 5000 rpm for 5 minutes. Imidazole, the epoxy resin curing agent, was dissolved in n-butanol solution at a mass ratio of 1:1 and then added to the MoS2@Co / Fe ternary composite absorbent and epoxy resin mixture. The first layer consisted of 5 parts ternary composite absorbent, 86 parts epoxy resin, and 9 parts imidazole solution, with a spray thickness of 2.1 mm. The second layer consisted of 10 parts ternary composite absorbent, 82 parts epoxy resin, and 8 parts imidazole solution, with a spray thickness of 1.8 mm. After spraying, the mixture was left at room temperature for 2 hours and then cured in an oven at 80°C for 2 hours.
[0085] The effective absorption bandwidth (RL≤-10dB) ranges from 4.16GHz to 7.92GHz, almost covering the entire C-band. Meanwhile, the reflection loss curve exhibits dual resonant peaks, with a reflection loss of -41.1dB at 4.8GHz and -27.5dB at 6.8GHz.
Claims
1. A method for preparing a coating for absorbing low-frequency electromagnetic waves in the C-band, characterized in that: 1) Add oxalic acid, thiourea, and selenium, tungsten, or molybdenum salts containing ammonium ions to deionized water to obtain a mixed solution; the molar ratio of the ammonium ion salt, oxalic acid, and thiourea is (0.5–2): (5–20): (20–80), and the tungsten, molybdenum, and selenium salts containing ammonium ions are ammonium tungstate, ammonium molybdate, and ammonium selenate, respectively; 2) Transfer the mixed solution obtained in step 1) into a reaction vessel, heat the reaction for 24-48°C, and then allow it to cool naturally to room temperature; 3) Obtain the grayish-black product from the bottom of the reactor in step 2) and wash it; 4) Dry the product obtained in step 3) to obtain transition metal dichalcogenide nano-self-assembled bodies; 5) The transition metal disulfide self-assembly is ultrasonically dispersed in deionized water, and then metal chloride and hexamethylenetetramine are added sequentially and stirred to react; the molar ratio of transition metal disulfide, metal chloride and hexamethylenetetramine is (0.5-2):(5-20):(50-100). 6) Transfer the mixed solution from step 5) to a reactor, heat and react, separate the reaction products, and wash them; 7) Dry the product obtained in step 6) to obtain a transition metal disulfide and metal hydroxide composite precursor; 8) The product obtained in step 7) is subjected to microwave treatment in a mixed gas atmosphere of argon and hydrogen to obtain a binary composite absorber of transition metal disulfide and magnetic metal. 9) Using the product obtained in step 8) as the raw material for the coating, the coating is sprayed onto the substrate to obtain a C-band low-frequency electromagnetic wave absorbing coating. The following steps are included when obtaining the coating: 9-1) The transition metal dichalcogenide magnetic metal composite absorber prepared in step 8) is mixed with epoxy resin and then dispersed. 9-2) Dissolve the epoxy resin curing agent imidazole in a n-butanol solution, with a mass ratio of imidazole to n-butanol of 1:1; 9-3) Mix the products obtained in steps 9-1) and 9-2) to obtain a coating; In the above steps, when preparing the coating for the first layer, the composite absorbent is 5-10 parts, the epoxy resin is 82-86 parts, and the imidazole solution is 8-9 parts. In the above steps, when preparing the coating for the second layer, the composite absorbent is 10-15 parts, the epoxy resin is 77-82 parts, and the imidazole solution is 8-9 parts. When preparing a double-layer electromagnetic wave absorbing coating, the thickness of the first layer is 1.8~2.1mm; the thickness of the second layer is 1.8~2.1mm; and the total thickness of the two electromagnetic wave absorbing layers does not exceed 4mm.
2. The method for preparing a coating for absorbing C-band low-frequency electromagnetic waves according to claim 1, characterized in that: In step 2), the reactor is a polytetrafluoroethylene reactor.
3. The method for preparing a coating for absorbing C-band low-frequency electromagnetic waves according to claim 1, characterized in that: In step 3), the supernatant of the reactants obtained in step 2) is discarded, and the gray-black product at the bottom of the reactor is collected. The product is washed with anhydrous ethanol and then centrifuged.
4. The method for preparing a coating for absorbing C-band low-frequency electromagnetic waves according to claim 1, characterized in that: In step 4), depending on the raw materials, the obtained transition metal disulfide nano-self-assembled bodies are tungsten disulfide, molybdenum disulfide, or selenium disulfide nano-self-assembled bodies.
5. The method for preparing a coating for absorbing C-band low-frequency electromagnetic waves according to claim 1, characterized in that: In step 6), after the reaction is complete, allow the solution to cool naturally to room temperature, filter under vacuum, and then wash with anhydrous ethanol and deionized water 3 to 5 times respectively.
Citation Information
Patent Citations
Composite coating structure for absorbing and preventing electromagnetic wave
CN101355866A
Binary composite structure optical absorbent and preparation method thereof
CN113583496A